Mongolian medicine Wulanwendusu-11 alleviates myocardial ischemia-reperfusion injury by modulating the intestinal microbiota and associated metabolic pathways - Wuyunsiqin; Bai, Tingting; Yang, Dandan; Hashentuya; Namila; Jin, Chelegeer; Tana; Zhao, Pengwei; Wang, Minjie; Menggenduxi (Frontiers in Microbiology, 2026)
ObjectiveWulanwendusu-11 (WLWDS-11) is a commonly used Mongolian medicine for treating cardiovascular diseases. However, its regulating effect on intestinal flora-host metabolism in relieving chronic myocardial ischemia-reperfusion injury (MIRI) is still unclear. Therefore, this study aims to systematically explore the cardioprotective mechanism of WLWDS-11 from the perspective of metabolic interaction between intestinal microbiota and host.MethodsC57BL/6J mice were randomized into six experimental groups: MIRI model, sham surgery, and treatment groups for compound Danshen dripping pills (CDDP) plus three dosages of WLWDS-11 (denoted WLWDS-11-L, WLWDS-11-M, and WLWDS-11-H). General physiological indicators of mice in each group were observed, body weight, myocardial structure and pathological features were assessed by electrocardiogram, plasma cardiac enzyme levels. The cardiac function of mice was obtained by echocardiography. Immunohistochemical staining was used to detect the pathological changes in the heart. Immunofluorescence assay was used to detect the degree of apoptosis. Metabolomics and metagenomics were used to analyze treatment effects on intestinal microbiota and metabolites. Integrated analysis of the enriched oxidative phosphorylation and necrosis and apoptosis pathways. qRT-PCR and western blot were used to detect the expression of COX4I1, NDUFB8, SDHA, TFAM, RIPK1, RIPK3, MLKL and TNF-α.ResultsWLWDS-11 (especially in high dose) can significantly improve the cardiac function, reduce the area of myocardial infarction and weaken apoptosis and fibrosis in MIRI mice. Metabolomic profiling revealed extensive metabolic alterations, pathway analysis implicated arginine/proline and unsaturated fatty acid metabolism, and hierarchical clustering identified specific correlations between differential flora (e.g., Kosakonia, Helicobacter spp.) and key metabolites. Integrated multi-omics analysis demonstrated that MIRI induces gut microbiota dysbiosis and systemic metabolic disturbances, characterized by the accumulation of oxidized lipids/lysophospholipids and disruption of critical metabolic pathways. The intervention of WLWDS-11 effectively reshaped the intestinal microbial community and made the metabolic spectrum return to normal. More importantly, correlation and network analysis confirmed the correlation between specific intestinal bacteria (such as Prevost, Kosakonia and Helicobacter) and host metabolites, and formed a flora-metabolite axis regulated by WLWDS-11. KEGG pathway analysis further confirmed the effects of the treatment on key pathways, including necrotizing apoptosis and oxidative phosphorylation. From the point of view of mechanism, WLWDS-11 reversed the mitochondrial dysfunction induced by MIRI by up-regulating the expressions of COX4I1, NDUFB8, SDHA and TFAM. By inhibiting the RIPK 1/RIPK 3/MLKL pathway and TNF-α, necrotizing apoptosis and inflammatory response are inhibited. These results suggest that WLWDS-11 may protect MIRI’s heart by regulating the metabolic pathway of flora.ConclusionWLWDS-11 positively reshaped the gut microbial environment by suppressing pathogenic bacteria and promoting beneficial strains, thereby fostering eubiosis, attenuating cardiac pathology, and ultimately conferring cardio protection. These findings identify WLWDS-11 as a potential candidate drug and provide a molecular mechanistic basis for the clinical treatment of MIRI.